Problemy polityki ekologicznej w Polsce - Zysnarska, Ewa (Ecological policy problems in Poland, 2006)
The article presents elements of ecological policy. It provides an introduction to the context for increasing public participation in sustainable development. Very important is international forum for exchanging ideas about the integration of ecological and economic principles defining sustainable development. Moreover, the author emphasizes the role of non-profit associations for environmental policy, and explains the ecological information concept of restoration, management and preservation of environmental quality.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1129, s. 370-378